Time-Dependent Structural Alteration of Rituximab Analyzed by LC/TOF-MS after a Systemic Administration to Rats. - Yuki Otani; Atushi Yonezawa; Masahiro Tsuda; Satoshi Imai; Yasuaki Ikemi; Shunsaku Nakagawa; Tomohiro Omura; Takayuki Nakagawa; Ikuko Yano; Kazuo Matsubara (PLoS ONE, 2017)
Therapeutic monoclonal antibodies (mAbs) have heterogeneities in their structures. Multiple studies have reported that the variety of post-translational modifications could affect the pharmacokinetic profiles or pharmacological potencies of therapeutic mAbs. Taking into the account that the structural modification of mAbs would affect the efficacy, it is worth investigating the structural alteration of therapeutic mAbs in the blood and the relationship between their structures and pharmacological effects. Herein, we have developed the method to isolate rituximab from plasma in which endogenous IgGs interfere the detection of rituximab, and successfully developed the analytical method with a liquid chromatograph time-of-flight mass spectrometer to detect the structure of rituximab in plasma with errors less than 30 parts per millions. Eight types of carbohydrate chains in rituximab were detected by this method. Interestingly, time-dependent changes in carbohydrate chains such as AAF (G2F) and GnGn (G0) were observed in rats, although the amino acids were stable. Additionally, these structural changes were observed via incubation in plasma as in the rat experiment, suggesting that a certain type of enzyme in plasma caused the alterations of the carbohydrate chains. The present analytical methods could clarify the actual pharmacokinetics of therapeutic mAbs, and help to evaluate the interindividual variations in pharmacokinetics and efficacy.